Mitochondrial flashes regulate ATP homeostasis in the heart - Xianhua Wang; Xing Zhang; Di Wu; Zhanglong Huang; Tingting Hou; Chongshu Jian; Peng Yu; Fujian Lu; Rufeng Zhang; Tao Sun; Jinghang Li; Wenfeng Qi; et al. (eLife, 2017)
The maintenance of a constant ATP level (‘set-point’) is a vital homeostatic function shared by eukaryotic cells. In particular, mammalian myocardium exquisitely safeguards its ATP set-point despite 10-fold fluctuations in cardiac workload. However, the exact mechanisms underlying this regulation of ATP homeostasis remain elusive. Here we show mitochondrial flashes (mitoflashes), recently discovered dynamic activity of mitochondria, play an essential role for the auto-regulation of ATP set-point in the heart. Specifically, mitoflashes negatively regulate ATP production in isolated respiring mitochondria and, their activity waxes and wanes to counteract the ATP supply-demand imbalance caused by superfluous substrate and altered workload in cardiomyocytes. Moreover, manipulating mitoflash activity is sufficient to inversely shift the otherwise stable ATP set-point. Mechanistically, the Bcl-xL-regulated proton leakage through F1Fo-ATP synthase appears to mediate the coupling between mitoflash production and ATP set-point regulation. These findings indicate mitoflashes appear to constitute a digital auto-regulator for ATP homeostasis in the heart.